Converting Corn Cobs into Briquettes in Braja Harjosari Village, Braja Salebah Subdistrict, East Lampung Regency - Sutrisno, Agus; Zakaria, La; Aziz, Dorrah; Nisa, Khoirin (Faculty of Mathematics and Natural Sciences - Universitas Lampung, 2025)
Corn cobs are agricultural waste that can be processed into an alternative firewood. Carbonization (pyrolysis) followed by briquetting is one method to process biomass into solid charcoal. According to a survey conducted, the large amount of corn cob waste is due to a lack of knowledge in processing waste which causes health and environmental problems. Converting corn cob waste into briquettes transforms it into a valuable commodity. In fact, transforming corn cob waste is essentially applying the zero waste concept to agricultural production systems. Based on potential and agreements with farmer groups, community members, and local government, this service activity was carried out. The productivity of the briquette charcoal business made from corn waste is increased through training and assistance.